Intermediate procedural and health status outcomes and the clinical care pathways after chronic total occlusion angioplasty: A report from the OPEN‐CTO (outcomes, patient health status, and efficiency in chronic total occlusion hybrid procedures) study. Issue 4 (27th October 2020) - Sapontis, James; Hirai, Taishi; Patterson, Christian; Gans, Benjamin; Yeh, Robert W.; Lombardi, William; Karmpaliotis, Dimitri; Moses, Jeffrey; Nicholson, William J.; Pershad, Ashish; Wyman, R. Michael; Spaedy, Anthony; et al.
Abstract: Background: No previous reports have described the comprehensive care pathways involved in chronic total occlusion percutaneous coronary intervention (CTO PCI). Methods: In a study of 1, 000 consecutive patients undergoing CTO PCI using hybrid approach, a systematic algorithm of selecting CTO PCI strategies, the procedural characteristics, complication rates, and patient reported health status outcomes through 12 months were assessed. Results: Technical success of the index CTO PCI was 86%, with 89% of patients having at least one successful CTO PCI within 12 months. A total of 13.8% underwent CTO PCI of another vessel or reattempt of index CTO PCI within 1 year. At 1 year, the unadjusted major adverse cardiac and cerebral event (MACCE) rate was lower in patients with successful index CTO PCI compared to patients with unsuccessful index CTO PCI (9.4% vs. 14.6%, p  = .04). The adjusted hazard ratios of myocardial infarction and death at 12 months were numerically lower in patients with successful index CTO PCI, compared to patients with unsuccessful index CTO PCI. Patients with successful index CTO PCI reported significantly greater improvement in health status throughout 12‐months compared to patients with unsuccessful index CTO PCI. Conclusion: CTO‐PCI in the real‐world often require treatment of second CTO, non‐CTO PCI or repeat procedures to treat initially unsuccessful lesions. Successful CTO PCI is associated with numerically lower MACCE at 1 year and persistent symptomatic improvement compared to unsuccessful CTO PCI. Understanding the relationship between the care pathways following CTO PCI and health status benefit requires further study.